Digital Marketing Communication of Entrepreneurship Curriculum in Islamic Boarding School: Case Study in Pesantren Sirojul Huda Bandung Regency West Java - Rachmawati, Indri; Pratama Putra, Raditya; Junita Triwardhani, Ike (COMMENTATE: Journal of Communication Management, 2024)
Entrepreneurship is a program that continues to receive significant support. In 2020, the Governor of West Java allocated hundreds of billions of rupiah to foster new entrepreneurs as part of the post-pandemic economic recovery. In Islam, trading (entrepreneurship) holds a prominent position, as highlighted in a hadith narrated by Ahmad, where the Prophet Muhammad (SAW) said, "You should trade because it contains nine doors of sustenance." Therefore, educating the younger generation, especially Muslims, to become resilient entrepreneurs is crucial. This research explores the integration of entrepreneurship programs within Islamic boarding school (pesantren) education. Using a qualitative methodology and case study approach, the study focuses on Sirojul Huda Islamic Boarding School in Bandung Regency. The school has introduced entrepreneurial training for students starting at the Tsanawiyah level. Key participants in this research include two school administrators as primary sources and students as secondary sources. Currently, the school offers two extracurricular programs for students interested in culinary arts and clothing production (convection). Future plans include expanding these activities. However, the program faces challenges due to a lack of professional management. For example, the school’s catering and convection services lack proper promotion through digital marketing. Findings suggest that incorporating Digital Marketing Communication into entrepreneurship education is essential and should be included in the official curriculum. This addition would enhance the entrepreneurial skills and knowledge of students, particularly within the Muslim community, and better prepare them for modern economic challenges.